2014
DOI: 10.1186/2047-2994-3-25
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of surgical site infections following caesarean sections at Bugando Medical Centre, Mwanza, Tanzania

Abstract: BackgroundSurgical site infection (SSI) is the second most common infectious complication after urinary tract infection following a delivery by caesarean section (CS). At Bugando Medical Centre there has no study documenting the epidemiology of SSI after CS despite the large number of CSs performed and the relatively common occurrence of SSIs.MethodsThis was a prospective cohort study involving pregnant women who underwent a CS between October 2011 and February 2012 at Bugando Medical Centre. A total of 345 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

38
160
11
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(215 citation statements)
references
References 34 publications
38
160
11
6
Order By: Relevance
“…In present study, a significant association was 144 observed between higher ASA grade and prevalence of SSI (Grade I, II and III: 4.3%, 23.1% & 20%; p<0.05). Various studies have shown that ASA score greater than 2 is a risk factor for development of SSIs [28][29][30][31]. Morgan et al [28] in their study observed that ASA score of more than two was associated with increase in risk of SSI by 1.52 times.…”
Section: Discussion:-mentioning
confidence: 98%
“…In present study, a significant association was 144 observed between higher ASA grade and prevalence of SSI (Grade I, II and III: 4.3%, 23.1% & 20%; p<0.05). Various studies have shown that ASA score greater than 2 is a risk factor for development of SSIs [28][29][30][31]. Morgan et al [28] in their study observed that ASA score of more than two was associated with increase in risk of SSI by 1.52 times.…”
Section: Discussion:-mentioning
confidence: 98%
“…Among 103 cases of discharge sent for culture and sensitivity only 54 cases (52%) yielded positive culture report .Studies conducted by Filbert J Mpogoro,1 Stephen E Mshana, also yielded only 48% culture positive cases [6] Of the 54 cases, 23(42.6%) cases were Klebsiella Species, 20 (37%) were Staphylococcus aureus ,9( 16.7%) cases were MRSA and 2 (3.7% ) cases were E coli. The most common organism causing SSI in abdominal surgeries is usualyE.coli .…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to less number of cases. Studies done by Leong G1, Wilson J, Charlett also prove that duration of surgery is directly proportional to SSI [5] SSI was diagnosed if any one of the criteria was present -localized swelling/edema at wound / redness, or discharge from the wound or positive organisms in the culture report.…”
Section: Discussionmentioning
confidence: 99%
“…Isolat lainnya termasuk 5 (22,7%) Klebsiella spp, 3 (13,6%) Escherichia coli, 2 (9,1%) Acinetobacter spp, 2 (9,1%) Pseudomonas spp, 1 (4,5%) Proteus spp, 1, (4,5%) Enterobacter spp, 1 (4,5%) Micrococcus spp, dan 1 (4,5%) koagulase negatif Staphylococcus spp. 6 Penggunaan antibiotik profilaksis pada intraoperasi secara tepat dapat mengurangi ILO. Antibiotik profilaksis diberikan kepada pasien dengan tujuan untuk mengurangi jumlah bakteri yang ada dan membantu pertahanan alami dari host sehingga infeksi dapat dicegah.…”
unclassified